2005
DOI: 10.2174/1389557053402738
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of P-Glycoprotein

Abstract: The aim of the present review is to summarize recent progress in identifying substrate binding domains of P-glycoprotein by photoaffinity labeling. Preferred substrate binding regions have been identified using a number of photoaffinity ligands, including anthracyclines, the quinazoline iodoarylazidoprazosine (IAAP), dihydropyridines, taxanes and propafenones. These studies allowed identification of protein regions, which are involved in ligand interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Protons from each CH 2 chain segment have the same chemical shift but could contribute differently to each cross-peak volume due to different contacts with the substrate. A better spatial resolution is offered by other NMR approaches such as 2 H NMR on selectively chain deuterated lipids or 13 C MAS NMR, as demonstrated for the antidepressants desipramine and imipramine (also PGP substrates). They have been found to show contacts down to the sixth of 14 carbons on the lipid acyl chain (26,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protons from each CH 2 chain segment have the same chemical shift but could contribute differently to each cross-peak volume due to different contacts with the substrate. A better spatial resolution is offered by other NMR approaches such as 2 H NMR on selectively chain deuterated lipids or 13 C MAS NMR, as demonstrated for the antidepressants desipramine and imipramine (also PGP substrates). They have been found to show contacts down to the sixth of 14 carbons on the lipid acyl chain (26,47).…”
Section: Discussionmentioning
confidence: 99%
“…So far, insight into drug location and interaction with membranes has relied on calorimetry (24), molecular modeling (25), 1 H, 14 N, and 31 P NMR spectroscopy (26,27), 1 H- 13 C dipolar coupling constants (26,28), 2 H order parameters (29,30), and fluorescence measurements (29,31). MAS-NOESY (magic angle spinning assisted nuclear Overhauser enhancement spectroscopy) has been shown by Gawrisch and co-workers to be a powerful tool in studying the distribution of the substrate within model lipid bilayers in multilamellar dispersions (32)(33)(34).…”
mentioning
confidence: 99%
“…Furthermore, MsbA is also in the ABC family of multi-drug resistance protein and confers drug resistance in bacteria and MsbA and P-gp share many common substrates. Thus, MsbA and its homology model may be used to explain the transport activities of the ABC transporter family in general [56], especially because the two transmembrane domains of both contain six α-helical segments that consist of the substrate transporting channel [55,56,59].…”
Section: Anthracycline Drug Resistance Is Mediated By Multi-drug Resimentioning
confidence: 99%
“…Nevertheless, an atomic detail structure of P-gp or of any other ATPdependent multidrug transporter is not available to date. Photoaffinity labeling studies have identified regions that are accessible for substrates (Peer et al, 2004). Atomic details of the substrate binding domain and of the dynamics of the transport process, however, still remain elusive.…”
mentioning
confidence: 99%